Natural places: Perceptions of wildness and attachment to local greenspace. (February 2019) - Colley, Kathryn; Craig, Tony
Abstract: Wildness is not only a quality associated with remote landscapes; it may be perceived to differing degrees in greenspaces in and around settlements. While place attachment in relation to rural wild land settings has been widely studied and wildness (or its analogue naturalness) appears to be a central dimension of sense of place and landscape preferences, little is known about the role of perceived wildness in attachment to the everyday green/blue environments that serve as important resources for local communities. At the same time, it remains unclear how perceptions of wildness in such places are constituted with respect to different forms of human influence. These issues were explored through a questionnaire survey of residents (N = 248) living in three study areas located along an urban-rural transect in North-East Scotland. Results indicated that different types of perceived human intervention (perceived levels of design and management) contributed differently to perceived wildness. Perceived design was inversely related to wildness, whilst also moderating the effect of perceived management on wildness. Place attachment was positively associated with perceived wildness, an effect which was not moderated by factors relating to individuals' relationship with the natural world as a whole. Highlights: Wildness was more strongly associated with perceived design than management. Perceived design moderated the relationship between management and wildness. Place attachment was positively related to both perceived wildness and management. Wildness plays an important role in users' sense of place in local greenspaces.